Swedish National Forest Inventory: Presence-absence vegetation data (1995-2017, discontinued sample) - Jonas Dahlgren (Swedish University of Agricultural Sciences, 2024)
The Swedish National Forest Inventory (NFI) is a sample based field inventory performed by the Swedish University of Agricultural Sciences (SLU). The annual inventory is undertaken on sample plots and this forms the basis for a large number of estimates. Data is collected across the whole of Sweden and statistics are published for all land use classes except urban land and sea and fresh water.

The data collection is focused on forest land and particularly productive forest land. Since year 2003 areas within formally protected land are included and since year 2016 non–coniferous alpine forest are included.

The sample size (number of permanent sample plots where presence/absence registrations are performed) was reduced by 50% from year 2018 and onwards. This dataset consists of the discontinued sample for the period 1995-2017, and supplements the data from the reduced sample available in the related dataset 'Swedish National Forest Inventory: Presence-absence vegetation data (1995-current)'.
Keywords: coverage; bottom layer; absence; rock surface; standardised inventory; pasture land; sampling event; field layer; subalpine woodland; forest land; mires; forest statistics; survey; stratified sampling; presence; alpine areas; Samplingevent; SAMPLING_EVENT; Biological Sciences; Biologi; Forest Science; Skogsvetenskap